Advanced Applications of Artificial Intelligence in Metallic Materials Processing - Panorios Benardos (Metals)
As the name of this Special Issue indicates, its aim was to highlight advanced applications of Artificial Intelligence (AI) in metallic materials processing, containing a final total of 12 published papers [...]